George Devine Treloar, le sauveur des Pontiques - Joëlle Dalègre (Cahiers Balkaniques)
Abstract: an Australian, George Devine Treloar, is celebrated both in Thrace and Australia as the savior of the Pontians. Who is he? Here is an opportunity to review the living conditions in Thrace from 1922-1923, the creation of the village of Thrylorio and the development of the local pontian identity.